Semi-analytical multidimensional algorithm for aircraft design optimisation - Šajn, Viktor (Strojniški vestnik, 2019)
The winner of American Institute of Aeronautics and Astronautics (AIAA)/Textron Aviation/Raytheon Missile Systems Design/Build/Fly (DBF) Competition 2019 was Edvard Rusjan team from Faculty of Mechanical Engineering, University of Ljubljana, Slovenia. Edvard Rusjan team use a strict scientific approach to beat opposing teams from most prestigious US Universities. Team developed a semi-analytic multidimensional algorithm for aircraft design optimization with an aim to maximize competition score in accordance with the competition rules. Two intermediate prototype models were produced and tested for single ground and three flying missions to fine tune algorithm empirical coefficients. Aircraft model aerodynamics was predicted with RANS numerical simulations and dynamic stability with Inviscid Panel method. By measurement in Low Turbulence Wind Tunnel the low drag of selected aircraft external load configuration was verified. Wing and fuselage of competition aircraft model named by Ljubljana students "Pretty Boy" were made of carbon-glass sandwich composite and Aramide honeycomb as sandwich filler. At final fly-off at TIMPA field in Tucson, in final flight mission team pilot Timotej Hofbauer with "Pretty Boy" scored 18 laps in 10 minutes time slot which was absolute record of competition. Runner-up Georgia Institute of Technology team was 22% slower and finished with 14 scored laps.
Keywords: aerodinamični upor; aerodynamic drag; carbon-glass sandwich composite construction; DBF competition 2019; DBF tekmovanje 2019; design parameters; Edvard Rusjan team; ekipa Edvarda Rusjana; kompozitna konstrukcija letala iz ogljikovega stekla; konstrukcijski parametri; number of laps in time slot; število krogov v časovnem režimu; take-off; vzlet